P‐9: Reduction and Mechanism of ESD Defect in IGZO‐TFT Formation. Issue 1 (29th May 2019) - Liu, Tianzhen; Duan, Xianxue; Xu, Dezhi; Cui, Haifeng; Zhang, Zhihai; Youn, YangSik; Chen, Junsheng; Lee, SeungKyu
Abstract : In this paper, "IGZO deposition" and "IGZO Photo" are found to be the critical steps that occurs for ESD in Oxide TFTs. The mechanism of ESD has been studied, furthermore, several improvement methods has been proposed.